2018
DOI: 10.1007/s40259-018-0274-5
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 Blockade in Cardiovascular Diseases: From Bench to Bedside

Abstract: Interleukin-1 (IL-1) is the prototypical pro-inflammatory cytokine that occupies an apical place in the inflammatory cascade and also modulates cardiac function, functioning as a soluble cardiodepressant factor. Preclinical research over the past 4 decades has shown that blocking IL-1 processing or activity favorably affects cardiomyocyte survival and cardiac function in experimental animal models, paving the way for clinical studies in patients with heart disease. The promising results of phase II clinical tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…and impaired left ventricular function (dP/dt max ) (9). Moreover, exposure to IL-1b impairs vascular endothelial function possibly via increased oxidative stress (36).…”
Section: Discussionmentioning
confidence: 99%
“…and impaired left ventricular function (dP/dt max ) (9). Moreover, exposure to IL-1b impairs vascular endothelial function possibly via increased oxidative stress (36).…”
Section: Discussionmentioning
confidence: 99%
“…HF is characterized by systemic inflammation, as shown by elevated circulating levels of inflammatory biomarkers in patients that increase with progression of the disease (25). For one, systemic inflammation may be the result of HF by means of tissue hypoperfusion and neurohormonal activation (26), or inflammation may play a pathophysiologic role in HF (27, 28). It is suggested that the pro-inflammatory state contributes to the development and progression of HF, not only by impairing myocardial function but also by affecting other organs and tissues and thereby adding to other aspects of the HF syndrome including cachexia and anemia (25).…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that I/R stimuli could induce the expression of GSDMD in the rat heart, while β-Asarone treatment markedly decreased the cleavage and activation of this protein, which was consistent with the level of caspase-1 activity. And IL-1β, a key proinflammatory cytokine which was closely associated with myocardial infarction and myocardial I/R injury, 29,30) also acted as an indicator of pyroptosis for its releasing style--through the pyroptosis pores in membrane. 31) Present results showed that the functional expressions of GSDMD also paralleled with the serum level of IL-1β.…”
Section: Dissussionmentioning
confidence: 99%